The female privilege. On celebrating International Women’s Day in state enterprises in the Polish People’s Republic - Kosztowna, Natalia (Studia Historiae Oeconomicae, 2015)
The article discusses the subject of celebrating International Women’s Day in the Polish People’s Republic (1952-1989). The author aims at showing the importance of this day in the public space - specifically in state enterprises. The article mainly attempts to assess whether those celebrations were inspired by the communist authorities and used to achieve some short- and long-term social goals, or if they allowed to establish or re-establish some kind of trust for the party in power. Empirical data are used to illustrate the phenomenon. The author points out that in the period of the Polish People’s Republic, there existed a certain privilege of being a women. This was evidenced by the prestige that the authorities of the time assigned to the celebration of Women’s Day and the fact that Men’s Day was not celebrated, or at least was much more marginal.